China's High-Speed Rail Technology An International Perspective (Advances in High-speed Rail Technology,, 2018)
This book presents cutting-edge theories, techniques, and methodologies in the multidisciplinary field of high-speed railways, sharing the revealing insights of elite scholars from China, the UK and Japan. It demonstrates the achievements that have been made regarding high-speed rail technologies in China from all aspects, while also providing a macro-level comparative study of related technologies in different countries. The book offers a valuable resource for researchers, engineers, industrial practitioners, graduate students, and professionals in the fields of Vehicles, Traction Power Supplies, Materials, and Infrastructure.